(untitled) - Finch, Byron J. (New York, NY, 2006)
There is no better book than Operations Now: Profitability, Processes, Performance to motivate your students to learn about operations management and how and why it is critical to success in business. The Second Edition retains its cutting-edge content and unique Resource/Profit Model, a conceptual framework that places operations management in a context of business financial performance
Keywords: Production management